Frekuensi Karier Streptococcus pneumoniae pada Populasi Dewasa Suku Akit Provinsi Riau - Rosdiana, Dani; Veronica, R. Merlinda; Harahap, Sari; Esha, Indi; Mardhatilah, Ashifa; Putri, Nabila; Safitri, Nuridha Audinia; Safari, Dodi; Sarassari, Rosantia; Ilmiawati, Cimi; Elliyanti, Aisyah (Jurnal Ilmu Kedokteran, 2024)
Stretococcus pneumoniae (S.pneumoniae) is a commonly colonized in healthy people that potentially to be transmitted directly to other individuals through droplets and as an invasive pathogen. The prevalence/ frequency of S. pneumoniae carriage in children is around 20-60%, while data of carriage’s frequency in adult population is still limited. Akit tribe is a tribe who lives in a group in the coastal rural area of Rupat Island. The high incidence of upper respiratory tract infection among Akit tribe and the location can be risk for S. pneumoniae carriage. Study aimed is to identify the frequency of carriage in the adult population of the Akit tribe. Nasopharyngeal swab was collected from healthy adults, then cultivated on agar media. Colonies suspected as S. pneumoniae then selected, then subjected to optochin test. S. pneumoniae confirmation were using automatic machine VITEK. We reported S. pneumoniae carriage rate was 7.8% (12 of 153 participants) among Akit tribe.